Community-oriented network measurement infrastructure (CONMI) workshop report. - claffy, kc (Computer communication review.)
This report summarizes issues discussed at the first CONMI workshop held on 30 March 2005 in Boston, Massachusetts. Sponsored by the National Science Foundation's Office of Cyberinfrastructure (OCI-0532233), the workshop was intended to begin a discussion regarding the viability and utility of a community-oriented network measurement infrastructure. This report was published 20 December 2005 online at: http://www.caida.org/workshops/conmi/.